2022
DOI: 10.3389/fonc.2022.852454
|View full text |Cite|
|
Sign up to set email alerts
|

Microbubbles Ultrasonic Cavitation Regulates Tumor Interstitial Fluid Pressure and Enhances Sonodynamic Therapy

Abstract: Sonodynamic therapy (SDT) is a promising treatment method for solid tumors. However, the high interstitial fluid pressure (IFP) in tumor tissues limits the accumulation of sonosensitizers. In the present study, microbubbles ultrasonic cavitation was used to regulate the tumor’s IFP and evaluate SDT effects. Rabbit VX2 tumor tissues were treated with microbubbles ultrasonic cavitation. The IFP of different tumor parts before and after cavitation was measured by the WIN method. The accumulation of the sonosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It also implies that ultrasonically enhanced blood flow may not promote tumor growth and metastasis. Previous study also suggested that therapeutic ultrasound with microbubbles induced perfusion enhancement does not increase tumor growth rate or metastasis in rabbit VX2 tumors, suggesting that USMC is a safe method to increase tumor perfusion ( 62 ).…”
Section: Discussionmentioning
confidence: 96%
“…It also implies that ultrasonically enhanced blood flow may not promote tumor growth and metastasis. Previous study also suggested that therapeutic ultrasound with microbubbles induced perfusion enhancement does not increase tumor growth rate or metastasis in rabbit VX2 tumors, suggesting that USMC is a safe method to increase tumor perfusion ( 62 ).…”
Section: Discussionmentioning
confidence: 96%
“…Attractively, UTMD can destroy tumor blood vessels in the site through cavitation to reduce adverse effects. And vascular rupture generated by disruption of micro- or nano-droplets with ultrasound can reduce IFP, break the pore size limitation between endothelial cells, and expand tissue space to facilitate drug penetration ( Ho and Yeh, 2017 ; Cao et al, 2018 ; Ho et al, 2018 ; Xi et al, 2022 ; Zheng et al, 2023 ). In light of the above theory, it is reasonable to speculate that the destruction of tumor vasculature by LIFU-TMD treatment caused incomplete vessel wall structure and decreased IFP, which could promote the penetration of anti-PD-L1 antibodies into tumors through the enlarged vascular space.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SDT needs to generate sufficient amounts of ROS, and the ROS produced should effectively be able to kill tumor cells. However, the high interstitial fluid pressure in pancreatic tumors, generated by the abundant tumor stroma, presents a challenge for the successful penetration and distribution of sonosensitizers in the tumor tissue (Xi et al, 2022). In addition, the hypoxic tumor microenvironment of pancreatic tumors inhibits the generation of ROS, and the high concentration of glutathione (GSH) in pancreatic tumors can consume the ROS produced by SDT, which in turn weakens the lethality to cells (Kshattry et al, 2019; Tang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%